Do Mock-Ups, Presentations of Evidence, and Q&As Help Participants Voice their Opinions During Focus Groups and Interviews About Supervised Injection Services?. (25th August 2021) - Kryszajtys, David T.; Rudzinski, Katherine; Chan Carusone, Soo; Guta, Adrian; King, Kenneth; Strike, Carol
Controversial facilities (e.g., supervised injection services (SIS), methadone clinics, and social housing) may require feasibility studies that asses their acceptability among community stakeholders before their implementation. However, controversies about these facilities may make stakeholders ambivalent or hesitant to express opinions about them because various sources of information disagree about their harms and benefits. We responded to this challenge by creating and piloting the use of "grounding aids" or tools, objects, and methods used before qualitative data collection to provide research participants with an experience in which they can learn about how the controversial facility operates in practice. Before interviews and focus groups in a recent SIS feasibility study we conducted, participants were introduced to three of these grounding aids: a physical mock-up of an SIS, a presentation regarding evidence on SIS, and a Q&A with SIS staff. We then asked additional questions in the interviews and focus groups about participants' experience with these grounding aids. With few exceptions, participants generally perceived the grounding aids to help them express their opinions without feeling that we were directing their opinions about SIS. Participants' reasons for this included that the grounding aids helped them experience unfamiliar aspects of SIS visually and concretely, served as a cue for questions and as a reference for discussions, and personalized SIS and its operations. We also observed that they voiced less hesitancy overall regarding SIS than participants in our previous feasibility studies where we did not employ these grounding aids before data collection. Researchers planning to study perceptions of controversial facilities or other phenomena about which sources of information tend to disagree on may want to consider creating, evaluating, and using grounding aids to improve participant responsiveness.